Upgrading techniques for transformation of biogas to bio‐CNG: a review. (16th February 2017) - Singhal, Shailey; Agarwal, Shilpi; Arora, Shefali; Sharma, Pankaj; Singhal, Naveen
Summary: Increasing consumption of fossil fuels and environmental concern has led to increased use of compressed natural gas (CNG) in the transportation sector. Keeping in view limited resources of CNG, biogas is advised as potential fuel to provide continuous supply of CNG in the form of bio‐CNG. Various technologies, that is, physical and chemical absorption (using water and amine solutions, respectively, for the absorption of carbon dioxide), pressure swing adsorption, membrane separation, and cryogenic separation, are available for purifying biogas and thus upgrading it, to bio‐CNG with about 95% methane. Among these, water scrubbing and pressure swing adsorption are the best technologies with respect to various aspects including cost; however, suitability of a technology is decided by various factors including size/quantity of biogas generation, targeted quality of biogas, site of application, and economics of process. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Biogas is a potential means of renewable energy. Its upgradation to bio‐CNG even increases its value making it equivalent to compressed natural gas in its properties and performance. Physical & chemical absorption, pressure swing adsorption, membrane separation, and cryogenic separation are important technologies widely available in the market for this purpose, each having its own advantages.